(untitled) (Innovative Technologica: Methodical Research Journal, 2021)
Students also make a number of mistakes when writing some letters of the alphabet. Teaching students to write continuously from 1st grade onwards improves the ability to write quickly and easily in these places. The development of students’ writing skills should continue from the time they graduate to the end of the school year.